2001
DOI: 10.1037/0021-9010.86.5.930
|View full text |Cite
|
Sign up to set email alerts
|

360° feedback: Accuracy, reactions, and perceptions of usefulness.

Abstract: This study examined how 360 degree feedback ratings and self-other rating discrepancies related to reactions to feedback, perceptions of feedback accuracy, perceived usefulness of the feedback, and recipients' receptivity to development. The results indicated that less favorable ratings were related to beliefs that feedback was less accurate and to negative reactions. Negative reactions and perceptions that feedback was less accurate were related to beliefs that the feedback was less useful. Those who found fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
398
2
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(425 citation statements)
references
References 44 publications
(56 reference statements)
19
398
2
6
Order By: Relevance
“…In an upward feedback field experiment study, Atwater, Waldman, Atwater, and Cartier (2000) reported that leaders who received lower ratings from their subordinates reduced their commitment to them after receiving the feedback. Likewise, Brett and Atwater (2001) reported that lower ratings received by over-estimators resulted in negative reactions such as anger and discouragement. Overestimation on the part of leaders may therefore affect subordinates' job satisfaction negatively and turnover intention positively.…”
Section: Self-other Agreement and Subordinates' Job Satisfaction And mentioning
confidence: 99%
“…In an upward feedback field experiment study, Atwater, Waldman, Atwater, and Cartier (2000) reported that leaders who received lower ratings from their subordinates reduced their commitment to them after receiving the feedback. Likewise, Brett and Atwater (2001) reported that lower ratings received by over-estimators resulted in negative reactions such as anger and discouragement. Overestimation on the part of leaders may therefore affect subordinates' job satisfaction negatively and turnover intention positively.…”
Section: Self-other Agreement and Subordinates' Job Satisfaction And mentioning
confidence: 99%
“…To date, the general consensus from research and practice has been that there are both benefits and potential problems associated with 360s, especially if used as an evaluation system rather than just as a personal development technique (Brett & Atwater, 2001). DeNisi and Griffin (2001) summarize the major advantages: (1) they provide ratees with information on how they are perceived by others; (2) they provide more information for improvement (by addressing weaknesses) than any other technique; and (3) ratings and feedback from different groups with special insights can be obtained.…”
Section: Digitalcommonsunledumentioning
confidence: 99%
“…In particular, positive feedback enhances individuals' perceptions of their response capability, which may bolster individuals' perceptions of the usefulness of the feedback (Martocchio & Webster, 1992). Brett and Atwater (2001), for example, found that lower 360 o feedback ratings from others (i.e., boss, peers) generated more negative reactions (i.e., angry, Reactions to Assessment 13 confused, discouraged), which in turn detrimentally impacted the perceived usefulness of the feedback. Based on this evidence, we predict that trainees who perform better on the pretraining assessment will have more positive utility perceptions.…”
Section: Hypothesis 3: Trainees' Pre-training Assessment Performance mentioning
confidence: 99%
“…It is often the case, however, that skill assessments are only loosely tied to specific developmental opportunities. A good example is multi-source feedback systems, which are frequently used to highlight individuals' weaknesses and developmental needs with the goal of stimulating self-directed learning and development (Brett & Atwater, 2001;Smither, London, Flautt, Vargas, & Kucine, 2003). In these situations, an important issue concerns the extent to which the assessment process motivates individuals to seek out development opportunities.…”
Section: Reactions To Assessment 33mentioning
confidence: 99%
See 1 more Smart Citation